PENGEMBANGAN E- GOVERNMENT DI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA SEMARANG - PRASETYO, SIDIQ; Warsono, Hardi (Journal of Public Policy and Management Review, 2017)
Semarang is the capital city of Central Java Province, Indonesia, consisting of various Kota District which in every agency has website in accessing information relating to main task and function of each agency. As in the Office of Education and Culture that has a website in providing information and services to the community. In a government in need of information network to improve public services in this case by utilizing Information Technology in the form of website (website). Utilization of Information Technology Communication in a government called the Electronic Government. Research aims to Know and analyze the development of e-Government (website) at the Department of Education and Culture of Semarang City, Knowing What are the obstacles encountered in the development of e-Government (website) at the Department of Education and Culture of Semarang City, Solutions to overcome the obstacles encountered in the development of e-Government (website) at the Department of Education and Culture of Semarang City. Techniques Data analysis using data reduction (data reduction), namely the selection process, concentration attention on simplification, abstraction, and transformation of rough data obtained in the field study. Data presentation (data display), namely the description of a collection of information is arranged that allows to make a conclusion And taking action. Conclusion drawing and verification. From the process of collecting data, the researcher looks for the meaning of every phenomenon obtained in the field, noting the possible explanation or explanation and configuration patterns, causality flow, and proposition. If the research is still ongoing, any specified conclusions will continue to be verified until a valid conclusion is reached. Research results The development of e-government is a development process through the stages of Preparation, Maturation, Stabilization, and Utilization in which there are supporting factors such as Government support, Resource Capacity, and Benefits provided that affect e-government development. Based on the results of observations and interviews with some informants, e-Government development in Semarang City still has some deficiencies that must be improved so that users like the community and other parties who use the official website of the Office of Education and Culture of Semarang City feel comfortable in accessing all information Has beenprovided by the official website of Semarang City.